Using of Ground Penetrating Radar (GPR) for investigate the subsurface archaeological features of Babylon, the ancient city (Mounts zoona) - Nehaba, Mohammed S.; Thabit, Jassim M.; Mohammed, Amar J. (Iraqi Journal of Science, 2019)
Ground Penetrating Radar (GPR) method has been used in the province of Babylon, the ancient city (constituted mounts zoona) archeological site The study area is located South of the city of Hilla by 40 km between longitudes 44˚ 24΄ 40˝ E to 44˚ 27΄ 00˝ E, and latitudes 32˚ 31΄ 10 ˝ N to 32˚ 33΄ 00˝ N,The type of GPR that used in the survey fieldwork was of Malå Geoscience / Sweden type (RAMAC /GPR). The constituted mounts zoona district are surveyed using Seventy – four parallel profiles trending S-N ,N-S , E-W and W-E using the available antenna 160 MHz and 450 MHz, with Five meter spacing between each other are acquired the round-trip survey was conducted for ease and speed of fieldwork for both antenna 160 MHz and 450 MHz taking this into consideration in the interpretation and take special area with dimensions 20*20 meter according to the first shape anomalies individual profiles with one meter between the old the profiles that spacing Five meter also direction longitudinal and transverse also the round-trip survey was conducted for ease and speed of fieldwork was surveyed depending on the result of the regional survey.It is found that the upper zone of the constituted mounts Zoona characterized by dried clay and sandy soil with brocken archaeological materials, The second zone shows a prominent low resistivity zone probably caused by the moisture in this region that reduces the resistivity. The thickness of this layer is different from parts of the site to the others. The third deeper zone is typical for archaeological walls. Some of the main anomalies, may refer to buried archaeological remains of clay brick wallsThe 2D and 3D view of the constituted mounts zoona show that the archaeological anomalies are concentrated mainly in the SE part of the district with higher values of the height of the archaeological walls that range between (6-8) meters and reach to more than (10) meters. At the parts of the study area some walls are with low height that range 4-6 meters.